Peremajaan (Replanting) Kebun Sawit Plasma Rakyat dan Kemiskinan Baru di Kecamatan Dayun Kabupaten Siak Provinsi Riau - Yunus, Wan Muhammad; Zulkarnain, Zulkarnain; Irsya, Habib (Universitas Riau, 2024)
This research aims to find out whether the rejuvenation of plasma palm oil owned by the people in Dayun District, Siak Regency will cause new poverty. This research was conducted in 2022. This research took samples from 3 (three) villages in Dayun District, Siak Regency, Riau Province. The basic method used in this research uses descriptive analytical methods. The data collection technique was direct interviews with a sampling of 30 people, from which 10 people were taken from each village. Based on research conducted, it was found that the implementation of oil palm rejuvenation held in Dayun District, Siak Regency did not increase new poverty. This situation can be seen from the farmers' income which is dominated by other oil palm farming businesses that have been prepared by farmers long before the oil palm rejuvenation took place. Generally, each farming household buys at least one plot (2 ha) of land in another area which is cultivated as an oil palm farming business which is expected to produce FFB (Fresh Fruit Bunches) when farmers carry out oil palm rejuvenation on other land.